2014
DOI: 10.1073/pnas.1412944111
|View full text |Cite
|
Sign up to set email alerts
|

The PML domain of PML–RARα blocks senescence to promote leukemia

Abstract: In most acute promyelocytic leukemia (APL) cases, translocons produce a promyelocytic leukemia protein-retinoic acid receptor α (PML-RARα) fusion gene. Although expression of the human PML fusion in mice promotes leukemia, its efficiency is rather low. Unexpectedly, we find that simply replacing the human PML fusion with its mouse counterpart results in a murine PML-RARα (mPR) hybrid protein that is transformed into a significantly more leukemogenic oncoprotein. Using this more potent isoform, we show that mPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…NRF2 ∆ETGE was predominantly localized in the nucleus, and PR‐S showed weakly granular nuclear staining and clustered cytoplasmic staining (Fig. A), due to the absence of PML‐NLS, as described previously . Immunofluorescence staining revealed that PR‐S and NRF2 colocalized in the nucleus rather than the cytoplasm (Fig.…”
Section: Resultssupporting
confidence: 80%
“…NRF2 ∆ETGE was predominantly localized in the nucleus, and PR‐S showed weakly granular nuclear staining and clustered cytoplasmic staining (Fig. A), due to the absence of PML‐NLS, as described previously . Immunofluorescence staining revealed that PR‐S and NRF2 colocalized in the nucleus rather than the cytoplasm (Fig.…”
Section: Resultssupporting
confidence: 80%
“…At therapeutic concentrations, ATO induces the sumoylation of both PML-RARA and PML, leading to their proteasomal degradation in an RNF4-dependant manner [29][30][31]. PML-RARA degradation by arsenic derepresses expression of differentiation genes, as well as allows reformation of PML nuclear bodies and restoration of senescence [32][33][34][35]. In addition, ATO targeting of the normal PML allele enforces NB nuclear bodies (NB) formation and contributes to therapy response.…”
Section: Current Understanding Of Classic Apl Pathogenesis and Treatmmentioning
confidence: 99%
“…Even AML dedifferentiation may occur and explain clinical relapses [150]. Apart from differentiation, a mechanistically distinct consequence of therapy is loss of APL self-renewal [33][34][35]. Clinically, this is reflected by a decrease in the burden of leukemic cells, restoration of normal hematopoiesis and eradication of the APL clone driving long-term survival.…”
Section: Available Data For Therapy Response In Variant Aplsmentioning
confidence: 99%
“…The immune system seems to be important for eliminating senescent cells involved in APL clearance [232,233]. Partner-mediated RARA dimerization is believed to be essential for arresting differentiation [234,235], and transformation requires the PML coiled-coil domain [236].…”
Section: Atra-ato In Frontline Therapymentioning
confidence: 99%